Charge storage in nanotubes: the case of a 2-1 electrolyte - Schmickler, W.; Henderson, D. (Condensed Matter Physics, 2017)
We consider a 2-1 electrolyte in contact with a narrow nanotube, which only allows one-dimensional storage
along the axis. The asymmetry does not allow an a priori definition of the potential of zero charge; instead,
the natural reference is the electrode potential at which both ions have the same electrochemical potential;
the value of the latter can serve as a measure of ionophilicity. Near this potential, ionophobic tubes are filled
with a dilute gas, ionophilic tubes are filled with a one-dimensional solid containing about the same number
of the divalent ions and the monovalent counterions, a structure that is stabilized by a strong screening of
the Coulomb interaction by an induced counter charge on the walls of the tube. The filling of the tube by the
application of an electrode potential exhibits a complicated pattern of interactions between the two kinds of
ions. Ми розглядаємо 2-1 електролiт в контактi з вузькою нанотрубкою, яка дозволяє лише одновимiрне накопичення вздовж осi. Асиметрiя не дозволяє апрiорi означити потенцiал нульового заряду; натомiсть,
природною точкою вiдлiку є потенцiал електрода, бiля якого обидва iони мають той же електрохiмiчний
потенцiал; значення останнього може служити для вимiрювання iонофiльностi. Поблизу цього потенцiалу iонофобнi трубки наповненi розрiдженим газом, iонофiльнi трубки є наповненi одномiрним твердим
тiлом, що мiстить приблизно однакове число двовалентних iонiв i моновалентних контрiонiв, стiйкiсть
структури забезпечується сильним екрануванням кулонiвської взаємодiї iндукованим зарядом на стiнках
трубки. Наповнення трубки шляхом прикладання електродного потенцiалу демонструє складну картину
взаємодiй мiж двома сортами iонiв.